2019
DOI: 10.1007/s11227-019-02828-3
|View full text |Cite
|
Sign up to set email alerts
|

A research of Monte Carlo optimized neural network for electricity load forecast

Abstract: In this paper, we apply the Monte Carlo Neural Network (MCNN), a type of neural network optimized by Monte Carlo algorithm, to electricity load forecast. Meanwhile, deep MCNNs with one, two and three hidden layers are designed. Results have demonstrated that 3-layers MCNN improves 70.35% accuracy for 7 weeks electricity load forecast, compared with traditional neural network. And 5-layers MCNN improves 17.24% accuracy for 7 weeks forecast. This proves that MCNN has great potential in electricity load forecast.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 14 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…Deep MCNNs with one, two and three hidden layers were designed at the same time. The results demonstrated that deeper MCNN performed better than shallow MCNN [34]. Yang et al introduced a GVM approximate calculation system based on field programmable gate array, which can effectively accelerate the calculation of GVM [35].…”
Section: B Alo and Gvmmentioning
confidence: 99%
“…Deep MCNNs with one, two and three hidden layers were designed at the same time. The results demonstrated that deeper MCNN performed better than shallow MCNN [34]. Yang et al introduced a GVM approximate calculation system based on field programmable gate array, which can effectively accelerate the calculation of GVM [35].…”
Section: B Alo and Gvmmentioning
confidence: 99%
“…General Vector Machine (GVM) [10,11], which has a basic structure of threelayer neural network, is designed as a mixer model of neural network and SVM. In fact, GVM is applicable to cases of lacking samples [12,13], and it has been successfully applied in time series forecast problem, such as electricity demand forecast [14]. Meanwhile, development of modern technology generates the demand for more accurate electricity forecast.…”
Section: Introductionmentioning
confidence: 99%